Advances in Grid and Pervasive Computing
DOI: 10.1007/978-3-540-72360-8_57
|View full text |Cite
|
Sign up to set email alerts
|

SEMU: A Framework of Simulation Environment for Wireless Sensor Networks with Co-simulation Model

Abstract: Abstract. This paper presents a framework of simulation environment (SEMU) which allows developers to understand the behavior of applications or protocols for a wireless sensor network (WSN) before deploying real nodes in a physical environment.For eliminating the gap between simulation and real deployment, SEMU has supported fast real code emulation by dynamic binary translation technique. SEMU also models the controlled environment as virtual operating system (Virtual OS) to coordinate the interactions of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…To ease study the behaviour of the specific application and protocol and help in understanding this behaviour before the actual deployment a framework of simulation environment (SEMU ) for WSN with co-simulation, hybrid, model was presented in [15]. The co-simulation model proposed in SEMU is similar to the three hybrid modes for WSN simulation as of that proposed for EmStar [6].…”
Section: Semumentioning
confidence: 99%
See 2 more Smart Citations
“…To ease study the behaviour of the specific application and protocol and help in understanding this behaviour before the actual deployment a framework of simulation environment (SEMU ) for WSN with co-simulation, hybrid, model was presented in [15]. The co-simulation model proposed in SEMU is similar to the three hybrid modes for WSN simulation as of that proposed for EmStar [6].…”
Section: Semumentioning
confidence: 99%
“…Then the event was distributed using the flooding protocol until all of the virtual nodes received it. It was reported that SEMU did run fast below 1250 virtual nodes [15]. When the number of virtual nodes is increased beyond 1250 it was reported that simulation time quickly increases due to the limited RAM that the simulation was carried on, which was 1.5 GB [15].…”
Section: Semumentioning
confidence: 99%
See 1 more Smart Citation
“…A number of sensor network simulators allow a mixture of simulated nodes and testbed nodes. This technique is often called hybrid simulation [12,15,23,24]. Although hybrid simulation is designed to increase the realism by running parts of the network in a testbed, repeatability is affected negatively.…”
Section: Related Workmentioning
confidence: 99%
“…To decrease the gap between simulation and testbed, hybrid simulation has been proposed [12,15,23,24]. Hybrid simulation contains both simulated and testbed sensor nodes.…”
Section: Introductionmentioning
confidence: 99%